Պետական հակաճգնաժամային քաղաքականության բարելավման և արդյունավետության բարձրացման ուղիները ՀՀ-ում - Կարեն Սարգսյան (ՀՀ ԳԱԱ հրատ.)
Несмотря на то, что возникающие в разные периоды экономические кризисы имеют свои особенности, тем не менее можно разработать набор стандартов отбора инструментов фискальной и денежно-кредитной политики в области государственного антикри-зисного регулирования, которые могут быть использованы при разработке государственой политики по преодолению кризисов. Despite the fact that the economic crises that occur in different periods proceed with certain peculiarities it is possible to elaborate a set of standards for the selection of fiscal and monetary policy instruments in the field of state anti-crisis regulation, which can be applied during the development of specific anti-crisis policy for overcoming crises.
Keywords: Economic Theory